Review of Literature on GAIT Based Human Identification: Addressing Challenges in GAIT Based Human Identification (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Gait is basically based on human locomotion that is resultant of cyclic and coordinated movements’ combination. The movements must have some pattern related with specific temporal. Human walking is a combination of coordinated and cohesive muscles and joints of the body movements. The researchers have shown interest in gait as its recognition results have shown a promising growth in the controlled environment. In this thesis, solutions are proposed for the real world by taking care of gait controlled situations like view conditions, resolution and fluctuation of gait patterns due to carrying clothes as well as goods. It is quite difficult to analyses the gait pattern when the subject has been occluded with clothes and bag on the back.